2007
DOI: 10.1007/s11859-006-0133-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and provably secure multi-recipient signcryption from bilinear pairings

Abstract: Abstract:Signcryption is a cryptographic primitive that performs signature and encryption simultaneously, at a lower computational costs and communication overheads than the signature-then-encryption approach. In this paper, we propose an efficient multi-recipient signcryption scheme based on the bilinear pairings which broadcasts a message to multiple users in a secure and authenticated manner. We prove its semantic security and unforgeability under the Gap Diffie-Hellman problem assumption in the random orac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…However, in this paper we propose that sender belonging to the internet host (certificateless environment) and receiver belonging to the Wireless Sensor Node-WSNs (IBC). Our scheme employed certificateless signcryption (CLSC) introduced by Barbosa and Farshim in 2008 [3] and also in 2010 LI et al, [5] produce a scheme based on Barbosa and Farshim. Signcryption is a cryptographic primitive proposed by Zheng [6], which provides signature and encryption simultaneously, and has lower computational cost and communication overhead than the signature-then-encryption approach.…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in this paper we propose that sender belonging to the internet host (certificateless environment) and receiver belonging to the Wireless Sensor Node-WSNs (IBC). Our scheme employed certificateless signcryption (CLSC) introduced by Barbosa and Farshim in 2008 [3] and also in 2010 LI et al, [5] produce a scheme based on Barbosa and Farshim. Signcryption is a cryptographic primitive proposed by Zheng [6], which provides signature and encryption simultaneously, and has lower computational cost and communication overhead than the signature-then-encryption approach.…”
Section: Motivationmentioning
confidence: 99%
“…Recently, a proved security certificateless signcryption scheme in the standard model was proposed by Liu et al [7] which requires five pairing operations and one exponentiation in signcrypt and designcrypt phase. LI et al [5] produce a scheme based on Barbosa and Farshim. Our choice of this technique was as a result of the above stated problem inherent in both PKI and IBC [8]based schemes and also the efficient introduced by [3] we also require that the computational cost of sensor nodes and the internet is low.…”
Section: Related Workmentioning
confidence: 99%
“…It has been extensively studied by numerous researchers in an attempt to enhance the efficiency and security of the original scheme proposed by Zheng in 1997 [2]. In particular, its extension to the multi-recipient setting has received much attention [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In [1], they claimed that the signcryption scheme was more efficient that that in [2] and showed that their scheme was secure against indistinguishability attacks and existential unforgeability attacks in the random oracle model. To satisfy the security requirements of multi-user setting, Li et.al also proposed a 1-to-n type of signcryption [3] in 2007. Meanwhile, they also showed that their scheme [3] was secure against existential unforgeability attacks.…”
Section: Introductionmentioning
confidence: 99%
“…To satisfy the security requirements of multi-user setting, Li et.al also proposed a 1-to-n type of signcryption [3] in 2007. Meanwhile, they also showed that their scheme [3] was secure against existential unforgeability attacks.…”
Section: Introductionmentioning
confidence: 99%